Financial development and economic growth in Indonesia: An ARDL-Bounds testing approach - Leli Sumarni (Economic Journal of Emerging Markets, 2019)
The objective of this paper is to analyze the influence of financial development on economic growth in Indonesia using quarterly time series data for the period of 2005 to 2016. It uses an Autoregressive Distributed Lagged (ARDL-bounds) testing approach to cointegration to estimate the relationships among the variables. The financial development indicators used in this paper are financial credit, financial asset, and third-party funding. Findings/Originality: The results of the ARDL model estimates indicate that the variable is cointegrated and there is a long-run relationship between the variables, and therefore, there is a long-term causal relationship. The long-run estimation results disclose a significant positive relationship between economic growth and financial development, where economic growth is found to be significantly influenced by financial development indicators.